An Analysis of Students’ Mastery of Vocabulary : at English Department of Universitas Putra Indonesia YPTK Padang at 2018/2019 Academic Year - Desi Andriani; Vera Sriwahyuningsih (Universitas Lancang Kuning, 2019)
Vocabulary is an important thing in English. Therefore, at university vocabulary is a compulsory subject for English language study program. Students cannot speak, write, listen, and read the reading texts when they do not have enough vocabulary to understand them. Thus, students should master vocabulary. The research is a descriptive one. Population is students of UPI YPTK Padang in 2018/2019 academic year. The sample of the research is students of English education faculty. They were thirty four students. The data were collected by using test and questionnaire. The test is given to know students’ ability in vocabulary mastery. It consists of thirty questions. It consists of matching test for giving definition of a word, filling blank space and finding new vocabularies from unarranged letters. The result of the test showed that different abilities of students in mastery vocabulary. The students can find new vocabularies from unarranged letters. This was an interesting activity for them. Then, in matching the vocabularies to the definitions or synonyms, the students also could do it. The questionnaire proved that students have good ability in mastery vocabulary but they have some difficulties related to the some aspects such as grammar and spelling.